Continuous improvement on maturity and capability of Security Operation Centres - Cengiz Acartürk; Murat Ulubay; Efe Erdur (IET Information Security)
Abstract This study addresses maturity and capability assessment of Security Operation Centres (SOC). It aims to contribute to continuous improvement for SOCs by proposing a complementary methodology that provides SOCs a self‐assessment capability. The method basically involves an assessment of the gaps between the current and the desired states of the organization and facilitates determining critical aspects that have priority. The proposed methodology is based on the define, measure, analyze, improve, and control methodology of the Six Sigma approach and offers a service‐oriented improvement process for SOCs. The applicability of the methodology is demonstrated by a case study. We evaluated subject matter experts’ reviews using simplified conversation analysis as a qualitative, content‐analysis approach.